Determination of FPGA Implementation of New LM-SPIHT Colored Image Compression with Reduced Complexity and Low Memory Requirement Compatible for 5G - Yasmine M. Tabra; Bayan Mahdi Sabbar (New Approaches in Engineering Research Vol. 10, 2021)
The growth of 5G mobile systems necessitates a shift in image processing. The required processing time, as well as the amount of space for uploading and downloading, represent these modifications. In this study, an image compression method based on WT (Wavelet Transform), LM-SPIHT (Listless-Modified Set Partitioning in Hierarchical Tree) coding, and an additional level of Runlength encoding is proposed. The SPIHT algorithm can be applied to both grey-scale and colored images. SPIHT displays exceptional characteristics over several properties like good image quality, fast coding and decoding, a fully progressive bit stream, application in lossless compression, error protection and ability to code for exact bit rate. The new implementation aims to reduce the amount of data needed to be stored, this is done in several stages, and also aims to reduce the amount of time required for processing. VHDL (Very High Descriptive Language) was used on the netFPGA-1G-CLM Kintex-7 board to implement the compression. The new implementation succeeded in reducing the complexity of the compression system and with minimized processing time.